2021
DOI: 10.3390/molecules26092703
|View full text |Cite
|
Sign up to set email alerts
|

Exploiting a New Approach to Destroy the Barrier of Tumor Microenvironment: Nano-Architecture Delivery Systems

Abstract: Recent findings suggest that tumor microenvironment (TME) plays an important regulatory role in the occurrence, proliferation, and metastasis of tumors. Different from normal tissue, the condition around tumor significantly altered, including immune infiltration, compact extracellular matrix, new vasculatures, abundant enzyme, acidic pH value, and hypoxia. Increasingly, researchers focused on targeting TME to prevent tumor development and metastasis. With the development of nanotechnology and the deep research… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
10
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 177 publications
(201 reference statements)
1
10
0
Order By: Relevance
“…Tumor microenvironment (TME) is characterized by weak acidity, high concentration of hydrogen peroxide (H 2 O 2 ), excessive glutathione (GSH), and hypoxia [ 1 3 ]. It has been well proved that TME not only plays an important role in the occurrence, development and metastasis of tumors [ 4 , 5 ], but also induces resistance to conventional anticancer treatments such as radiotherapy and chemotherapy, resulting in poor prognosis [ 5 , 6 ]. Nevertheless, TME could also be exploited to realize certain specific cancer treatments owing to its notable difference to normal tissues [ 7 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Tumor microenvironment (TME) is characterized by weak acidity, high concentration of hydrogen peroxide (H 2 O 2 ), excessive glutathione (GSH), and hypoxia [ 1 3 ]. It has been well proved that TME not only plays an important role in the occurrence, development and metastasis of tumors [ 4 , 5 ], but also induces resistance to conventional anticancer treatments such as radiotherapy and chemotherapy, resulting in poor prognosis [ 5 , 6 ]. Nevertheless, TME could also be exploited to realize certain specific cancer treatments owing to its notable difference to normal tissues [ 7 ].…”
Section: Introductionmentioning
confidence: 99%
“…Nevertheless, TME could also be exploited to realize certain specific cancer treatments owing to its notable difference to normal tissues [ 7 ]. In addition, normalization of TME may in turn improve tumor therapy outcome [ 4 ]. Thereby a large number of TME-responsive cancer treatment strategies have been developed in recent years [ 8 10 ], including chemodynamic therapy (CDT) [ 11 13 ] and hypoxic-sensitive chemotherapy [ 14 , 15 ].…”
Section: Introductionmentioning
confidence: 99%
“…There may be low levels of glucose and other nutrients, as well as changes in temperature, all associated with various alterations in tumor cell metabolism [60]. While the heterogeneity of the tumor microenvironment sometimes makes it difficult to adequately characterize tumors [61], this has spawned interest in developing new nanotechnology therapeutic strategies to improve not only drug delivery conditions and directly destroy tumor cells, but also alter the balance between neoplastic cells and their microenvironment. Therefore, intelligent systems have been developed for the administration of drugs that respond to stimuli, and therapeutic agents can be activated by endogenous or exogenous stimuli [62,63].…”
Section: Drug Carriersmentioning
confidence: 99%
“…For example, Lei et al reported that polymeric micelles having pH and temperature dual-responsive properties accelerate the release rate of anticancer drugs at an acidic pH and a higher temperature [ 20 ]. From these points of view, stimuli-responsive nanocarriers have great potential in tumor targeting, because the physiological properties of the tumor microenvironment are quite different from their normal counterparts (i.e., tumor tissues are characterized as having an acidic pH, abnormal redox status, abundant extra- or intra-cellular enzymes and elevated expression of various molecular receptors) [ 22 , 23 , 24 , 25 ]. Therefore, the abnormal status of a tumor microenvironment provides a tumor targeting opportunity for polymeric nanocarrier-based drug delivery [ 26 ].…”
Section: Introductionmentioning
confidence: 99%